ANT 2011/12: AWI airborne Accumulation Radar data over western DML around EDML, eastern DML over the Sør Rondane Mountains, and over Atka Bay (GEA and WEGAS Projects) - Daniel Steinhage; Wilfried Jokat; Veit Helm (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWI Accumulation Radar (ACCU) system during the Antarctic season of 2011/12. The profiles cover western Dronning Maud Land around EDML, eastern Dronning Maud Land over the Sør Rondane Mountains, and over Atka Bay. The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.